Pelaksanaan Undang-Undang No 14 Tahun 2005 Tentang Guru dan Dosen Terhadap Peningkatan Profesional Guru Pendidikan Agama Islam di SMA Negeri 1 Taba Penanjung - Adam Nasution (Institut Agama Islam Negeri Bengkulu, 2019)
Abstract: Implementation of Law No. 14 of 2005 Concerning Teachers and Lecturers Towards the Professional Improvement of Islamic Education Teachers in State Senior High School 1st Taba Penanjung Professionalism is something that is not negotiable for teachers. Therefore, the government has issued Law no. 14 of 2005 concerning Teachers and Lecturers. Its implementation has not been evenly distributed throughout Indonesia. This study aims to describe the implementation of these regulations towards improving Teacher Professionalism at Taba Penanjung High School 1 which includes: a) learning planning b) learning process c). tutoring d) learning assessment. The method used is descriptive qualitative with data sources derived from teachers, principals, and documentation. Data collection techniques are observation, interview and documentation. From the results of the study it can be concluded the implementation of Law No. 14 of 2005 concerning teachers and lecturers has been conducted by teacher. Includes professionalism competencies: Abstrak : Pelaksanaan Undang-Undang No 14 Tahun 2005 Tentang Guru dan Dosen Terhadap Peningkatan Profesional Guru Pendidikan Agama Islam di SMA Negeri 1 Taba Penanjung Profesionalitas merupakan hal yang tidak bisa ditawar lagi. Oleh karena itu, pemerintah telah menerbitkan UU no. 14 Tahun 2005 Tentang Guru dan Dosen. Implementasinya belum merata di seluruh Indonesia. Penelitian ini bertujuan untuk mendeskripsikan Implementasi peraturan tersebut terhadap peningkatan Profesionalisme Guru Pendidikan Agama Islam di SMA Taba Penanjung yang meliputi: a) perencanaaan pembelajaran b) proses pembelajaran c). bimbingan pembelajaran d), penilaian pembelajaran. Metode yang digunakan adalah deskriptif kualitatif, sumber data berasal dari guru, kepala sekolah, dan dokumentasi. Teknik pengumpulan data adalah observasi, wawancara dan dokumentasi. Hasil penelitian disimpulkan bahwa pelaksanaan undang-undang No 14 Tahun 2005 tentang guru dan dosen meliputi kompetensi profesionalisme secara keseluruhan telah dilaksanakan oleh guru.